Synthesis and vibrational study of phosphate-sulfate fluorapatites Ca10-xNax(PO4)6-x(SO4)xF2 (0≤ x ≤6) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
A series of phosphate-sulfate fluorapatites Ca10-xNax(SO4)x(PO4)6-xF2 has been synthesized by the solid-state reaction at high temperature. The samples were characterized using X-ray diffraction, Infrared spectroscopy and Raman scattering spectroscopy. X-ray diffraction study shows that these materials crystallize in the hexagonal system with P63/m as space group. Infrared and Raman spectra are reported and band assignments are made.